Diagnostic Dilemmas in Carpal Tunnel Syndrome and Cervical Spine Disorders: A Comprehensive Review - Yuki Hara; Yuichi Yoshii (Diagnostics)
Carpal tunnel syndrome (CTS) and cervical spondylosis (CS) are both common diseases, yet differentiation between the two is sometimes necessary. However, there are few evidence-based reviews on the differentiation of these conditions. This review examined the literature on the diagnosis of CTS and CS, focusing on how to distinguish between them. The analysis is divided into four categories: clinical symptoms, physical examination, diagnostic imaging, and electrodiagnosis. A total of 281 studies are reviewed, revealing a major issue: the inclusion criteria for defining each disease varies widely across studies. Understanding this limitation, the conclusion drawn is that no single clinical symptom, test, or imaging evaluation can be deemed uniquely reliable for diagnosing CTS or CS. Therefore, it is essential to apply the most up-to-date knowledge, conduct thorough examinations, and perform necessary tests for each patient to achieve a confident and accurate diagnosis.